Shame, Honor Culture: Women's Resistance and Double Surveillance in Short Stories by Abdullah and Jarrar - Evania Alya Camila; Djohar, Hasnul Insani (Universitas Dian Nuswantoro, 2025)
This research discusses how female characters in short stories by Shaila Abdullah and Randa Jarrar experience shame and honor culture, double surveillance, and women’s resistance. This study aims to explore how honor and shame operate as mechanisms of patriarchal control, and how women navigate social pressures both in local and diasporic contexts. Using a qualitative method, this research analyzes textual elements, including dialogue and narration to examine these issues. Patriarchy Theory by Sylvia Walby, Intersectionality Theory by Kimberlé Crenshaw, and Postcolonial Subaltern Theory by Antonio Gramsci are applied to explain how gender, culture, and social expectations shape women’s experiences. The results show that the main characters face double surveillance from family and society, creating psychological and social constraints, yet they enact subtle forms of resistance to assert autonomy and identity. In conclusion, this research highlights the persistence of honor culture as a social control mechanism and the strategies women employ to reclaim freedom and dignity.